2018
DOI: 10.1002/jlb.mr0318-097r
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte subsets in cancer immunity: Friends or foes

Abstract: Although immune-based therapy is proving to be a success in several cancer types, only a set of patients appear to respond to immune checkpoint blockade including PD-1 and CTLA-4. A better understanding of the crucial components of cancer immunity is therefore necessary. T lymphocytes, a key element, are found within the tumor microenvironment and seem to be critical in determining the efficacy of immune surveillance. In this review, we will depict the pro-and antitumor roles of major T cell subsets in distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 163 publications
(226 reference statements)
0
102
0
Order By: Relevance
“…Lymphocytes play a vital role in influencing immune responses to tumors. Whether lymphocytes mount an immune response or a promote immune tolerance toward tumor cells is influenced by a number of factors including, cytokines, tumor cell immunoregulatory molecules, and secreted proteins, as reviewed by Chraa et al (53). In addition many recent advancements in NSCLC therapy act to alter T-cell responses.…”
Section: Leukocytes and C-met Expressionmentioning
confidence: 99%
“…Lymphocytes play a vital role in influencing immune responses to tumors. Whether lymphocytes mount an immune response or a promote immune tolerance toward tumor cells is influenced by a number of factors including, cytokines, tumor cell immunoregulatory molecules, and secreted proteins, as reviewed by Chraa et al (53). In addition many recent advancements in NSCLC therapy act to alter T-cell responses.…”
Section: Leukocytes and C-met Expressionmentioning
confidence: 99%
“…T lymphocytes play a crucial role in shaping the immune response against cancer. Multiple studies have demonstrated the presence of T lymphocytes in various types of mammary gland neoplasms [19]. A recent study has shown that lymphocytes comprise the primary population of inflammatory cells infiltrating mammary tumors regardless of their histological type [6].…”
Section: Discussionmentioning
confidence: 99%
“…We then compared the frequency profile of Vβ subfamily T cells in AML patients and found relatively high or low frequency of Vβ subfamily CD4+ or CD8+ T cells in AML. It is well known that different T cell subset and Vβ subfamily T cells have different functions based on antigen epitope recognition by different TCRs, indicating skewed proliferation of Vβ subfamily T cells in AML, and such T cell proliferation may be activated by a clonally expanded AML‐associated antigen. These so‐called tumor‐specific cytotoxic T cells may display cytotoxic activity against AML cells .…”
Section: Discussionmentioning
confidence: 99%